Case Report: Neuroendocrine carcinoma of the breast: a review of the literature and illustration of six cases - Nazire E. Albayrak (Frontiers in Medicine)
“Primary neuroendocrine breast carcinoma (NEBC) is an underdiagnosed subtype of breast cancer, which includes small cell (SCNEC) and large cell neuroendocrine carcinomas (LCNEC). Accurate diagnosis remains challenging given their low incidence; misclassification as invasive breast carcinoma of no special type (IBC-NST), invasive ductal carcinoma (IDC), or a metastatic neuroendocrine carcinoma may occur. Cases with any component of adenocarcinoma and well-differentiated neuroendocrine tumors were excluded. A search of the pathology database (2012–2024) revealed six female patients (27–85 years) with a final pathologic diagnosis of NEBC (stages IA–IV), including four diagnosed with LCNEC and two with SCNEC. Even though most NEBC cases (5 of 6; 83%) were of the luminal subtype, five of six patients (83%) developed distant metastases within 4 years of the initial diagnosis. Molecular profiling of six cases revealed common alterations in the FGF/FGFR and PI3K/AKT/mTOR pathways. In summary, primary neuroendocrine carcinomas of the breast display aggressive behavior. However, they are more likely to harbor certain alterations, such as activating PIK3CA mutations and FGFR1 amplification, which can be of therapeutic value. The Ki-67 index, unlike in the pancreas and gastrointestinal tract, is not suitable for grading neuroendocrine neoplasms (NENs) of the breast. However, it can still serve as a tool for risk stratification, similar to its use in luminal-type breast cancer.